(3OQGSGJ aj GdEYdGe hGdEYdGf GdSjGMjs - (3eUWai jhSa(B, (3cGajs ((3YeGf(B:s (3OGQ GdMGeO ddfTQ hGdJhRjY (B,s, 2015)
(3eaghe GdGYdGe h GdSjGMI h GdYdGbI HjfgeG h GhdhjGJ GdGYdGe GdSjGMj h GdJNWjW GdGYdGej GdSjGMj aj ehGLgI GdGReGJ h GdGYdGe GdSjGMj aj ehGLgI GdGReGJ GdSjGMjI ceG Je GdJWQb Gdi eaghe h WHjYI GdGYdGf h GdJQhjL GdSjGMj h eGgjI GdGYdGf GdSjGMj h JCKjQ GdGYdGf aj OhGaY GdGfSGf GdSjGMjI hhSGFd GdGYdGf GdeSJNOeI aj GdGYdGf GdSjGMj h cPG GdYdGbGJ GdYGeI GdSjGMjI h GdGfJQfjJ h CKQg aj GdSjGSGJ GdJQhjLjI GdSjGMjI h JfejI GdShb GdSjGMj h MedI JNWjW GdJShjb GdSjGMj h MedI GdGbfGY h GdJaGhV h GdOYGjI GdSjGMjI(B.s
(3eQGLY U(B. 301s
Keywords: (3GdEYdGe (B- (3GdEYdGf s; (3GdEYdGfs; (3GdSjGMIs